Green practice on consumer-based green brand equity: Mediating role of green brand attachment - Rezka Zilmy Ramanda (Journal of Management and Business Insight, 2025)
Purpose-This study aims to determine the effect of green practices on consumer-based green brand equity through green brand attachment as a mediating variable. To build strong consumer-based green brand equity, Wardah needs to implement appropriate green practice strategies. In addition, Wardah needs to build strong green brand attachment to increase consumer-based green brand equity. Methodology–Sampling was conducted using purposive sampling techniques. The sample consisted of 155 Wardah consumers in Indonesia. The questionnaire was distributed online and filled out by respondents. The data obtained from respondents was then tabulated and processed using Smart PLS 4.0. This study used validity and reliability tests to ensure the quality of the research instruments, as well as hypothesis testing to analyze the effect between variables based on respondent data. Findings-This study proves that green practices have a positive effect on green brand attachment and consumer-based green brand equity. Green brand attachment has a positive effect on consumer-based green brand equity. In addition, green brand attachment has also been proved as a partial mediator in the relationship between green practices and consumer-based green brand equity. The results of this study indicate that consumers form emotional bonds with brands that consistently implement green practices. Consumers who have emotional attachments will play a strategic role in increasing overall brand equity and competitive position in the green market. Research Limitations-The limitations of this study lie in the small number of samples and its focus solely on Wardah products. Therefore, the findings of research cannot be used as a reference to describe the respondents' views or the conditions of other products. Novelty-This research is expected to contribute to the skincare and makeup industry so that companies can implement green practices and green brand attachment. The implementation of these two things can contribute positively to consumer loyalty and equity.